Energy consumption of direct current galvanostatic zinc removal from viscose production wastewater - Novotný, Ladislav; Karásková, Aneta; Kuchtová, Gabriela; Mikulášek, Petr; Dušek, Libor (Springer, 2022)
The work provided information on the energy consumption E-e by direct current galvanostatic separation of zinc from ZnSO4 solutions under conditions close to the electrodeposition of zinc from viscose production wastewaters. The E-e values were displayed depending on the corresponding values of current densities i and electrical conductivities of solutions kappa in the form of 3D diagrams. The diagrams showed that E-e grew significantly with increasing i, with a significant influence of kappa. In the analysis of the present processes and other desirable directions of research, both previous findings from polarographic/voltammetric electrolysis (usually collected at lower current densities) and the outlined new treatments to technological/separation electrolysis (on the contrary, usually at higher values of current densities) were applied. The obtained data can serve as a reference data in further research to reduce the energy consumption of the technology used.
Spotřeba energie stejnosměrného galvanostatického odstraňování zinku z odpadních vod z výroby viskózy
Keywords: direct current electrolysis; galvanostatic deposition; zinc; industrial waters; viscose production; polarography/voltammetry; elektrolýza při stejnosměrném proudu; galvanostatická depozice; zinek; průmyslové vody; výroba viskózy; polarografie/voltametrie